2018
DOI: 10.1038/s41598-018-22399-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of T cell lymphoma infiltration process at the colon

Abstract: The infiltration and proliferation of cancer cells in the secondary organs are of great interest, since they contribute to cancer metastasis. However, cancer cell dynamics in the secondary organs have not been elucidated at single-cell resolution. In the present study, we established an in vivo model using two-photon microscopy to observe how infiltrating cancer cells form assemblages from single T-cell lymphomas, EL4 cells, in the secondary organs. Using this model, after inoculation of EL4 cells in mice, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, our macro‐observations of EL4‐LG cells by luminescence imaging could not only detect the hepatosplenic infiltration of EL4 cells but also that of other organs such as lung and bones including femur or tibia (Supplemental Figure S1A). In addition, Ueda et al recently showed that single EL4‐GFP cell movement during infiltration into colon could be detected by a two photon microscopy system, which is the same as our micro‐observation system of liver infiltration. Therefore, the combination of macro‐ and micro‐imaging technologies using luminescence and fluorescence allowed easy assessment of the temporospatial spread and unexpected infiltration of lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, our macro‐observations of EL4‐LG cells by luminescence imaging could not only detect the hepatosplenic infiltration of EL4 cells but also that of other organs such as lung and bones including femur or tibia (Supplemental Figure S1A). In addition, Ueda et al recently showed that single EL4‐GFP cell movement during infiltration into colon could be detected by a two photon microscopy system, which is the same as our micro‐observation system of liver infiltration. Therefore, the combination of macro‐ and micro‐imaging technologies using luminescence and fluorescence allowed easy assessment of the temporospatial spread and unexpected infiltration of lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this, two reasons are postulated. On the one hand, the primary human T cells with a size of 8 µm as described by Renner et al are much smaller than the murine EL4 cell line cells with 11 µm, as described by Ueda et al [38,39]. Using these values, the volume of an EL4 cell is approximately 2.6 times higher than a human T cell's volume.…”
Section: Cellular Content Of Spion Citratementioning
confidence: 94%
“…The responses of liver metastatic tumor cells and host stromal cells to chemotherapeutics in living mice were observed at the single-cell level after the red fluorescent protein-expressing human colorectal cancer cells (HT29) were inoculated into the spleen of green fluorescent protein-expressing nude mice [ 104 ]. GFP- or RFP-labeled T-cell lymphoma infiltration into the colon blood vessels of black C57BJ/6 mice was also observed using similar approaches [ 105 ]. Furthermore, the long-wavelength lights can produce second-harmonic generation (SHG) to image collagen fibers and allow the imaging of extracellular matrix changes (such as collagen stiffness) which is one of the hallmarks in cancer metastasis [ 106 ].…”
Section: Single-cell Imagingmentioning
confidence: 91%